KINERJA JANGKA PANJANG DAN LIKUIDITAS PASCA IPO DI PAPAN UTAMA DAN PENGEMBANGAN BURSA EFEK INDONESIA - Suherman Suherman (University of Merdeka Malang, 2015)
The purposes of this study were to examine and to compare the long-term performance of IPO firms on mainand development boards and to determine and to compare the liquidity of IPO firms on main and developmentboards. The sample of this study covered 59 IPO firms consisting of 32 firms listed on main board and 27 firmslisted on development board between 2010 and 2012. The results showed that one, two and three-years afterIPO, the long-term performance of IPO firms on the main and development boards were not statisticallydifferent, and one year after IPO, the liquidity of IPO firms on the main and development boards were notstatistically different.